RESPONSE OF DRILL SOWN FINGER MILLET [ELEUSINE CORACANA (L.)] TO PRE AND POST EMERGENT HERBICIDES - M. K. PRASHANTH KUMAR; B. G. SHEKARA; C. M. SUNIL; B. G. YAMUNA (The Bioscan, 2015)
The predominant weed floras observed in the experimental plot were Eleusine indica (L.) Gaertn., Dactyloctenium aegyptium. Commelina benghalensis, Ageratum conyzoides, Croton bonplandianum, Celosia argentia, Ocimum canum and Cyperus rotundus. Among different herbicides pre-emergence application of bensulfuron methyl (0.6% G) + pretilachlor (6.0 % G) at 10 kg ha-1 recorded significantly lower weed population of 20.33 per 0.25 m2 and weed dry weight of 7.56 g per 0.25 m2 as compared to unweeded check (172.33 no. and 58.44 g per m2, respectively). However, the grain yield and straw yield (3291 and 5208 kg ha-1, respectively) were significantly higher with pre-emergence application of bensulfuron methyl (0.6 % G) + pretilachlor (6.0 % GR) at 7.5 kg/ha as compared to unweeded check (814 and 1373 kg ha-1, respectively). Finally it can be concluded that pre- emergence application of bensulfuron methyl (0.6 % G) + pretilachlor (6.0 % G) @ 7.5 kg ha-1 (pre mix formulation) resulted in higher grain yield.